Perspectives on Platform Regulation Concepts and Models of Social Media Governance Across the Globe (Volume 1) - Bayer, Judit; Holznagel, Bernd; Korpisaari, Päivi; Woods, Lorna (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Online social media platforms set the agenda and structure for public and private communication in our age. Their influence and power is beyond any traditional media empire. Their legal regulation is a pressing challenge, but currently, they are mainly governed by economic pressures. There are now diverse legislative attempts to regulate platforms in various parts of the world. The European Union and most of its Member States have historically relied on soft law, but are now looking to introduce regulation. Leading researchers of the field analyse the hard questions and the responses given by various states. The book offers legislative solutions from various parts of the world, compares regulatory concepts and assesses the use of algorithms. With contributions by Izumi Aizu, Enni Ala-Mikkula, Alexandre Alaphilippe, Natalie Alkiviadou, Alejandro Aréchiga Morales, Siwal Ashwini, Judit Bayer, Jörg Becker, Konrad Bleyer-Simon, Elda Brogi, Shun-Ling Chen, Poren Chiang, Michael Geist, Gerard Goggin, Giovanni De Gregorio, Sarah Hartmann, Maximilian Hemmert-Halswick, Maria Carolina Herrera Rubio, Bernd Holznagel, Peng Hwa Ang, Richard Janda, Jan Christopher Kalbhenn, Juliya Kharitonova, Kristiina Koivukari, Päivi Korpisaari, Jacob Mchangama, Trisha Meyer, Kilian Müller, Larissa Sannikova, Mårten Schultz, Nicole Stremlau, Maria L. Vazquez, Kuo-Wei Wu and Lorna Woods.